Laparoscopic cholecystectomy in anemia patients: a retrospective cohort study - Al-Mulhim, Abdulrahman Saleh (International Surgery Journal, 2018)
Background: Preoperative anemia is associated with adverse outcomes after surgery, but no evidence study demonstrates this risk after laparoscopic cholecystectomy. This study aimed to measure the prevalence of preoperative anemia, and to assess its effect on early clinical outcome in laparoscopic cholecystectomy patients. Methods: Data of 6342 consecutive laparoscopic cholecystectomy patients between Januarys 1995 to January 2015 were evaluated. Preoperative anemia was defined as a hemoglobin level of less than 120gm/l in female, and less than 130gm/l in male. Logistic regression used for analysis. Results: Preoperative anemia identified in 37.4% of laparoscopic cholecystectomy patients and it more prevalence in women. Analysis showed that patients with severe [odds ratio1.83 (95% Confidence interval 1.62-3.66)], moderate [odds ratio 1.21 (95% Confidence interval 1.11-1.38)], and mild [odds ratio 1.04 (95% Confidence interval 0.91-1.13)] anemia had higher morbidity than those with normal preoperative hemoglobin. Conclusions: Anemia is common among laparoscopic cholecystectomy patients, and it is associated with more complications.